Pengaruh Ukuran Perusahaan, DER, ROA, dan Pajak Penghasilan terhadap Praktik Income Smoothing - Mahendra, Putu Rian; Jati, I Ketut (E-Jurnal Akuntansi; Vol 30 No 8 (2020), 2020)
Income smoothing is one of the ways the company management manipulates earnings information. This research uses panel data from manufacturing companies listed in Indonesian Stock Exchange (BEI) in the period from 2013 to 2017 to analyze the effect between cash holding, firm size, growth, dividend payout ratio, and leverage to income smoothing. This results of this study are that companies size has a significant negative effect, debt to equity ratio doesn’t have a significant effect to income smoothing, return on asset and income tax have a positive and significant effect to income smoothing. Keywords: Income Smoothing; Company Size; Debt To Equity Ratio; Return On Asset; Income.